Alternating Minimization Method for Total Variation Based Wavelet Shrinkage Model (Communications in Computational Physics, 2010)
In this paper, we introduce a novel hybrid variational model which generalizesthe classical total variation method and the wavelet shrinkage method. Analternating minimization direction algorithm is then employed. We also prove that itconverges strongly to the minimizer of the proposed hybrid model. Finally, some numericalexamples illustrate clearly that the new model outperforms the standard totalvariation method and wavelet shrinkage method as it recovers better image detailsand avoids the Gibbs oscillations.